Chronic Coronary Syndrome: Medical Therapy or Myocardial Revascularization? - Rocha,Antônio Sérgio Cordeiro da (2022)
Abstract The best therapeutic strategy for chronic coronary syndrome (CCS) is still controversial. The lack of contemporaneity of medical treatment in many randomized clinical trials prior to the large-scale use of statins, antiplatelet agents, anti-diabetic drugs with cardiovascular protection, and changes in life habits with well-established goals limits the applicability of such studies in current clinical practice. Medical treatment is the only therapeutic option capable of reducing atherosclerotic damage and, therefore, of acting effectively in preventing the progression of this disease. The purpose of this brief review is to critically analyze the main contemporary studies that confront medical treatment with myocardial revascularization in CCS.